A Y6-based polymerized small-molecule acceptor with non-conjugated alkyl linkages for efficient all-polymer solar cells. (December 2021) - Wu, Xiaomin; Hao, Xiangyu; Deng, Ping; Chen, Huipeng
Abstract: A polymerized small-molecule acceptor, NC-PY6, has been newly designed and successfully synthesized. NC-PY6 contains a rigid conjugated Y6-derived fused-ring small acceptor SY6 and a non-conjugated alkyl chain as the linkage. Similar to SY6, NC-PY6 exhibits the narrow bandgap of 1.44 eV and the low-lying lowest unoccupied molecular orbital energy level (−3.92 eV), which match with the known wide-bandgap polymer donor D18. The D18:SY6 based polymer solar cells showed a power conversion efficiency (PCE) of 13.1% with a voltage loss of 0.58 V. The all-polymer solar cells (all-PSCs) based on D18:NC-PY6 blend film gave an encouraging PCE of 12.3% with a voltage loss of 0.57 V. The results demonstrate the potential of molecular design strategy of polymerizing small-molecule acceptor with the non-conjugated alkyl chain as the linkage for new type of polymer acceptors for high-performance all-PSCs. Graphical abstract: Image 1 Highlights: A polymerized small-molecule acceptor, NC-PY6, has been newly designed and successfully synthesized. NC-PY6 contains a rigid conjugated Y6-derived fused-ring small acceptor SY6 and a non-conjugated alkyl chain as the linkage. The D18:NC-PY6 based all-PSCs achieves a PCE of 12.3%.